FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI GAMBIR (Uncaria gambir) DI DESA CIPANG KIRI HULU KECAMATAN ROKAN IV KOTO - ARI IRAWAN; Kusmiati; Fitriana, Laily (SUNGKAI, 2025)
Before 2023, the price of gambir in Cipang Kiri Hulu Village, Rokan IV Koto Subdistrict, reached IDR 100,000 per kg. However, the following year, the price drastically dropped to IDR 30,000 per kg. The impact of this decline in gambir farmers' income was heavily felt by the community of Cipang Kiri Hulu Village, where the village's economy, which was previously highly dependent on the agricultural sector, particularly gambir, became severely affected. Therefore, the objectives of this study are to analyze the income of gambir farmers in Cipang Kiri Hulu Village, Rokan IV Koto Subdistrict, in 2023, and to analyze the factors of land area, age of farmers, education level, labor force, gambir price, production quantity, and production costs that affect the income of gambir farmers in Cipang Kiri Hulu Village, Rokan IV Koto Subdistrict. The research method used is quantitative, with multiple linear regression analysis techniques. The results show that the average production of gambir farmers reaches 2,102 kg, with a total income of IDR 111,966,528. Fixed costs for farming tools and variable costs such as herbicide, repairs, and external labor total IDR 9,324,368, resulting in an income of IDR 102,642,160. The t-test results show that the age of farmers, education level, gambir price, production quantity, and production costs significantly affect income, while land area and labor force do not. This regression model explains 100% of the variability in gambir farmers' income, with an Adjusted R Square value of 1,000.